Prevalence and Outcome of Cesarean Section at Gandaki Medical College Teaching Hospital and Research Centre, Pokhara, Nepal - Gurung, Rubina Tamrakar; Gurung, G; Shrestha, R; Gurung, T; Sharma, P (Journal of Gandaki Medical College-Nepal, 2017)
Introduction: Gandaki Medical College Teaching Hospital is providing specialized obstetrician and gynecologist services since last one decade. Objectives: This study was conducted to know the prevalence and outcome of cesarean section at Gandaki Medical College Teaching Hospital and Research Centre during 2013 – 2015 A.D. (2070 – 2072 B.S.). Methods: It was a retrospective study of women undergoing cesarean section from 2013 to 2015 A.D. (2070 – 2072 B.S.). Results: During the period of three years 2013 – 2015 A.D. (2070 –2072 B.S.) otal deliveries were 2627. Among total deliveries cesarean section was performed in 1084 patients (41.26%). In 1084 patients 803 (74%) cesarean sections were performed as an emergency and 281(26%) were elective. In this study 15 to more than 35 years old patients were enrolled. Among cesarean sections done, 52% were primigravida, 46% were para and 2% were grandmulti. The indications for cesarean section were CPD (28%), fetal distress (25%), previous cesarean (14%), mal presentation (7%), premature rupture of membrane (5%), pre-eclampsia (6%), failed induction (5%), bad obstetric history (2%), antepartum hemorrhage (1%), and twins (1%). Conclusion: This study at Gandaki Medical College Teaching Hospital and Research Centre provided the prevalence, outcome and different indications of cesarean section which is life saving for both mother and newborn. And also the study can be useful to the hospital to improve facilities for safe motherhood and safety of newborn. Journal of Gandaki Medical College Volume, 09, Number 2, July December 2016, Page: 1-6